The MPTP Story - Langston, J. William (J Parkinsons Dis, 2017)
The identification of MPTP, a relatively simple compound which causes selective degeneration of the substantia nigra after systemic administration, has had an a significant impact on the understanding and treatment of Parkinson’s disease (PD) over the last 30 years. This article is prefaced by the intriguing “medical detective story” that lead to the discovery of the biological effects of MPTP in humans. The steps that lead to the unraveling its mechanism of action and their impact on research into pathways underlying nigrostriatal degeneration are reviewed. The impact of the animal models that have been developed utilizing MPTP is also described with a focus on the translational implications of MPTP-related research. These include use of MAO-B inhibitors aimed at neuroprotection in PD and the importance of a stable primate model for PD which was utilized to better understand the circuitry of the basal ganglia, and the identification of the subthalamic nucleus as a target for deep brain stimulation. Finally, the results of a broad range of epidemiologic studies aimed as assessing the impact of environmental factors in PD that have been inspired by MPTP are summarized, including the discovery of other neurotoxicants (rotenone and paraquat) with parkinsonogenic effects. Overall, this article attempts to describe how the discovery of this nigral neurotoxicant began, where it is currently, and what the future may hold.